La construction discursive de l’identité collective. Le cas des formules : au nom de la Rzeczpospolita et au nom de la Pologne - Dyoniziak, Jolanta; Pirogowska, Ewa (Studia Romanica Posnaniensia, 2024)
The article attempts to analyze the discourse formulas: on behalf of Rzeczypospolita and on behalf of Poland in the speeches of the presidents of the Third Polish Republic (1995-2023). The aim is to describe the potential of these formulas in the context of constructing the collective identity. The authors continue the debate undertaken in the previous publication (Dyoniziak & Pirogowska, 2023) and show on the basis of 1000 presidential speeches written on www.prezydent.pl that the proper name Rzeczpospolita has greater identity potential than the name Polska in creating a national community.